2023
DOI: 10.1007/s12161-023-02514-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Optical Response as a Food Authentication: Investigation of Non-linear Optical Properties of Edible Oils by Spatial Self-Phase Modulation (SSPM) Method

Abstract: The non-linear optical responses of cherry seed oil, avocado seed oil, and sesame oil were studied by observing spatial self-phase modulation (SSPM) in oil samples using a continuous wave laser beam. The non-linear refraction coe cients and third-order non-linear susceptibility of edible oils were estimated to be and , respectively, based on the intensity-dependent number of observed symmetric diffraction rings. Also, we examined the spatial self-phase modulation technique to investigate the authenticity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Several recent studies have shown that vegetable oils have significant NLO properties [8,[12][13][14][15]. However, as far as we know, no studies have been conducted on the NLO response of virgin cherry kernel oil (VCKO) with a 532 nm laser beam wavelength; this paper fills that gap.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Several recent studies have shown that vegetable oils have significant NLO properties [8,[12][13][14][15]. However, as far as we know, no studies have been conducted on the NLO response of virgin cherry kernel oil (VCKO) with a 532 nm laser beam wavelength; this paper fills that gap.…”
Section: Introductionmentioning
confidence: 93%
“…The importance of the design of optical devices, such as modulators and switchers, has also led researchers to discover and introduce new materials that can be used to advance the fields of photonics and communications [4][5][6][7]. On the other hand, the utilization of NLO responses has recently gained prominence as a viable approach to authentication and fraud detection in various materials [8,9]. In general, optical nonlinearity is associated with changes in material properties, such as the refractive index and absorption coefficient, caused by exposure to high-power light [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the phase difference between any two beams having the same wave vector equals 2πm, interference of the beams occurs. The rings in the SSPM pattern directly depend on the phase shift suffered by the laser beam [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%